SLUM TOURISM VS PESONA INDONESIA (Comparative Study of Tourism Promotion Concepts in Indonesia and Effectiveness Theory) - Widagdo, Haidi Hajar; Feriyanti, Yang Gusti; Indriani, Indriani; Kurniawan, Ramdhan; Mahmudin, Tono (ITB AAS Indonesia Surakarta, 2024)
Abstract Pesona Indonesia and Slum Tourism are two different branding concepts and have different tourist branding goals. Therefore, this research aims to analyze and compare the two tourism branding concepts and add effectiveness theory. This research is qualitative research with an exploratory approach. The data used in this research is secondary data that researchers obtained from books, scientific articles, credible websites, and a number of other sources that are commonly used in every research. These data were analyzed using the stages of data collection, data selection, data reduction, and drawing conclusions. The results of this research show that first The Indonesian tourism branding concept